Letter - Lizaso, Jose I. de
1937-07-06 -2- the Admiralty has issued instructions to all ships not to enter Santander owing to the alleged blockade. Should further details be received, I shall inform you, for I feel sure that you will use all your influence so that His Majesty's warships may be instructed to protect shipping on the high seas and to prevent the stoppage of British vessels outside territorial waters by the rebels. The blockade of Santander is undoubtedly a farce on the same lines as the blockade of Bilbao to expedite the taking of the city by starvation of the civil population. As you have already done so much for the Basques, I trust you will not now abandon them, but will do all that is possible to forward evacuation and alleviate the plight, of those who remain. Believe me, Yours sincerely Jose I. de Liasazo Sir Walter Citrine, K.B.E. 292/946/11/71(ii)